Buffering dan Nearest Neighbor Analysis pada Google Maps dalam Penyediaan Data Sektor Kepariwisataan - Fadellah, Putri Kurnia; Marsisno, Waris (Politeknik Statistika STIS, 2023)
So far, the recording of tourism facilities uses the survey method with several drawbacks, so that web scraping is an alternative for collecting data on tourism facilities. This study aims to collect data on tourism facilities using Google Maps web scraping, find out distribution patterns and tourism potential, and analyze the affordability of accommodation locations and food and drink providers to tourist attraction objects. The results showed that there were 5,149 accommodations, 2,085 tourist attraction objects, and 4,421 food and drink providers. Tourism facilities are clustered in South Bali. Gianyar, Badung and Denpasar are potential areas in the tourism sector. For buffer analysis, a 5Km ring buffer was used, resulting in 99.94% of accommodation and 99.95% of food and drink providers in Bali Province being very close to tourist attractions. Meanwhile for the 20Km buffer, it was found that all accommodation and food and drink providers in the Province of Bali are within reach of tourist attractions. Buffer analysis was also carried out with ring buffers μ+σ, μ+2σ, and μ+3σ, there were 97.79% of accommodations and 98.62% of food and drink providers in Bali Province that were accessible by location.